Enhancing Students’ Oral Communication Ability with the Demonstration Method in Procedure Text at Vocational High School - La Ede, Muhammad Asrafil Husein; Sunra, La; Kadir, Jus Sudarsih (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This study aims to improve students' speaking skills in procedure text by using demonstration method integrated with Culturally Responsive Teaching. This study used a collaborative classroom action research. A total of 36 students from class X AKL 2 SMK Negeri 1 Kendari became the subjects and one English teacher became the collaborator of this research. The results showed that the percentage of students' speaking ability was still very low at 25%. According to the facts discovered, the learning process has not gone as intended. Finally, there was a notable improvement following the use of the demonstrative method coupled with CRT (Culturally Responsive Teaching) which reached 36.11% in cycle I and 97.22% in cycle II. This shows that this demonstration method is very effective to be used by teachers in improving students' speaking skills because it can make the learning process more active, creative, and the ability of students to increase so that the atmosphere of learning becomes more fun.Keywords: Speaking, Procedure Text, Demonstration Method, CRT.